Optimasi Kondisi Pelarutan Logam Au dalam Endapan Placer dengan Proses Hidrometalurgi (Jurnal Geomine, 2019)
Gold obtained by isolating it from gold ore rocks. The hydrometallurgical process with aqua regia as a reagent is used to isolate gold from its alluvial deposits. This research was conducted to determine the optimum time of the hydrometallurgical process and how much the mass of dissolved Au. In this research sample were taken at three different points located in the Katingan River in Central Borneo with the depth of each samples is three meters from the water surface, then samples were leached using aqua regia with a span of 5, 10, 20, 60, 100 and 120 minutes. The data used were Au concentration data obtained from samples that have been previously leached and analyzed using the AAS (Atomic Absorption Spectrometry instrument) then processed using x and y curves to get the optimum time and mass of dissolved Au obtained using the equation. The research resulted concentration of Au at the time of leaching with a span of 5, 10, 20, 60, 100 and 120 minutes at each samples in each location in sequence at first location was 11.07mg/L, 10.68mg/L, 11.02mg/L, 11.23mg/L, 2.21mg/L, 0.51mg/L with dissolved Au mass 1.27x10-3gr, 1.22x10-3gr, 1.26x10-3gr, 1.12x10-3gr, 2.54x10-4gr and 5.87x10-5gr. Second location is 656mg/L, 587mg/L, 584mg/L, 625mg/L, 645mg/L, 210mg/L with dissolved Au mass of 7.54x10-2gr, 6.75x10-2gr, 6.71x10-2gr, 7.18x10-2gr, 7.41x10-2gr and 2.41x10-2gr. Third location is 261mg/L, 931mg/L, 625mg/L, 631mg/L, 639mg/L, 915mg/L with dissolved Au mass of 3x10- 2gr, 1.07x10-1gr, 7.18x10-2gr, 7.25x10-2gr, 7.34x10-2gr and 1.05x10-1gr. The result has shown that the most optimum time for the hydrometallurgical process in alluvial deposits is at 5 minutesbecause it produces the most optimum concentration of Au and Au mass under the stable of aqua regia conditions.